The Effect of Electronic Services Quality on Trust-Building in Online Customers of Tehran’s Brokerage Firms - mahdi mahmoudsalehi; Behrooz Dorri; Khalil Safari (Journal of Information Technology Management)
Knowledge management is influenced by many variables such as organizational structure, leadership style, organizational culture, information technology etc. We can spot organizational structure and climate as a framework and infrastructure can be considered in implementing successful knowledge management. Previous studies examined these variables in the implementation of knowledge management. In this study we investigated the influence of organizational structure and climate on knowledge management and mediator role of social interaction has been checked. Examining the mediator role of social interaction is the research innovation. In this study a sample of 148 companies in Iranian automotive industry has been selected. The results of structural equation model analysis support a mediating social interaction between organizational structure and climate with KM.